Change perception towards engineering - Ts. Rozainah Ibrahim - Siti Nurfarmy, Ibrahim (2021)
PEKAN, 27 June 2021 - Pursuing an engineering programme at an institution of higher learning (IPT) does not mean the students will become engineers only.